Difference Blood Pressure and Stres When Exam Practice Histology and Exam Practice Anatomy Online on College Student of Medicine in the Time of a Pandemic - R. W. Susilowati; Dayang Annaya Salsabila; Miranda Sukmawati; Dini Widianti (Nusantara Science and Technology Proceedings, 2022)
Covid-19 pandemic has many make the change on living humans, including system previous education in Indonesia conducted by stare advance but now conducted online, Ministry Education and Indonesian Culture publish the letter circular year 2020 about learning from House as preventing the spread of Covid-19. Education at the faculty medical demand student for could do practice in reach competence of course Thing this Becomes challenge alone good for lecturer, student nor institution education. Destination from the study this is for knowing difference description pressure blood and stress when exam practice histology and anatomy on college student-faculty medical University Yarsi. Method study manifolds observational analytic with cross-sectional design, determination sample using consecutive sampling on FK Yarsi students batch 2019. Measure pressure blood using an electronic sphygmomanometer and the stress is measured with the DASS (Depression Anxiety Stress Scale). Results study obtained on measurement pressure blood one week before the exam and 3 hours before exam obtained significant result (p 0.017) and results from DASS measurement obtained results that are not means (p 0.632). Conclusion pressure blood students who follow exam practice histology and anatomy have meaningful difference and statistical stress measurement no mean.